Headache and pregnancy - Melhado, Eliana Meire; Galego, Andressa Regina (Headache Medicine, 2012)
Headache in pregnancy is a peculiarity of woman life phase. Correct diagnosis in pregnancy is the best thing for a management gold standard. Some secondary headaches that mimic migraine may begin during pregnancy, and can be caused by vasculitis, brain tumor, pituitary tumor, arteriovenous malformation, sinus disease, idiopathic intracranial hypertension, subarachnoid hemorrhage, stroke, cerebral venous thrombosis, pre-eclampsia and eclampsia. These headaches must be correctly diagnosed. At the conclusion, if a pregnant patient presents primary headache, it will be necessary to treat her. The classic teratogenic risk occurs from the 29th day to the 70th day of gestation. Women with severe headache during this period should be treated because nausea and vomiting in association with pain can be teratogenic to the fetus. Non-pharmacological techniques are effective for acute and preventive treatment and should be applied. If drugs are necessary, will be choose minimal doses and medications that causes fewer problems in pregnancy. Management of pregnant women with migraine should be done with caution, keeping in mind the low level of scientific evidences.